2014
DOI: 10.1162/pres_a_00180
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Macroexpressions and Microexpressions in Computer Graphics Animated Faces

Abstract: Due to varied personal, social, or even cultural situations, people sometimes conceal or mask their true emotions. These suppressed emotions can be expressed in a very subtle way by brief movements called microexpressions. We investigate human subjects' perception of hidden emotions in virtual faces, inspired by recent psychological experiments. We created animations with virtual faces showing some facial expressions and inserted brief secondary expressions in some sequences, in order to try to convey a subtle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 38 publications
4
22
1
Order By: Relevance
“…Seeing the significant effect of verbal information on affect, the influence seems to be consistent here as well. In general, a happy microexpression was discerned better, aligned with previous research, where participants recognized microexpressions of happiness very well (Queiroz et al, 2014).…”
Section: Results Of Experimentssupporting
confidence: 88%
See 2 more Smart Citations
“…Seeing the significant effect of verbal information on affect, the influence seems to be consistent here as well. In general, a happy microexpression was discerned better, aligned with previous research, where participants recognized microexpressions of happiness very well (Queiroz et al, 2014).…”
Section: Results Of Experimentssupporting
confidence: 88%
“…Previous human-computer interaction studies showed that positive facial expressions are generally perceived as more trustworthy (Torre et al, 2020), while extreme facial expressions lead to feelings of eeriness (Mäkäräinen et al, 2014) and can have a negative influence on the perceived sincerity (Stephens et al, 2019). We found that the same holds true for microexpressions, also confirming that happiness is generally better recognized, aligned with Queiroz et al (2014). This helps understand how to create digital humans that users perceive well and, thus, can likely connect with, instead of how they view CAs now: in purely transactional terms (Clark et al, 2019).…”
Section: Joining the Discourse On Trustworthy Digital Agentssupporting
confidence: 82%
See 1 more Smart Citation
“…Limiting this assessment is lack of empirical clarity when the virtual human is part of a learning system containing significant supporting information such as text boxes. The level of contribution of virtual human micro-expressions [63] and verbal tones [64] remain current topics in human-virtual human engagement in role playing research. Virtual human research with the previously mentioned SimSensi and MACH, wearable agents [65,66], virtual peers and companions [67,68] and virtual patients [69,70] may provide further insights.…”
Section: Conclusion Limitations and Future Directionsmentioning
confidence: 99%
“…In 2014, Queiroz et al [2] presented a pioneer work where the authors investigate if people perceive the facial micro expressions in a similar way with CG characters than with real people. It is interesting because micro and macro facial expressions can be used to provide more realistic characters in many applications as games and simulations.…”
Section: Introductionmentioning
confidence: 99%